Symmetry of positive solutions of a p-Laplace equation with convex nonlinearites - Keqiang Li; Shangjiu Wang (AIMS Mathematics, 2023)
In this paper, we consider the symmetry properties of the positive solutions of a $ p $-Laplacian problem of the form